Regulation of Nuclear Factor Kappa-Light-Chain-Enhancer of Activated B Cells (NF-κβ) in Inflammatory Bowel Diseases - Zaidi, Deenaz; Wine, Eytan (Frontiers in Pediatrics, 2018)
Inflammatory bowel diseases (IBD), encompassing both Crohn Disease (CD) and ulcerative colitis (UC) are globally prevalent diseases, impacting children of all ages. The hallmark of IBD is a perturbed immune system that leads to continuous inflammation in the gut and challenges optimal treatment. Nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κβ), a nuclear transcription factor, plays a major role in gut homeostasis and contributes significantly towards a balanced, homeostatic immune system. Dysregulation in the NF-κβ pathway and factors that regulate it lead to a state of uncontrolled inflammation and altered immunity, as typically observed in IBD. Levels of proinflammatory cytokines that are regulated through NF-κβ are increased in both CD and UC. Genes known to activate NF-κβ, such as, Nucleotide-binding oligomerization domain-containing protein 2 (NOD2) and Interleukin 23 (IL-23) are associated with IBD. Factors involved in inhibition of NF-κβ, such as A20 and TOLLIP are also affected in IBD, resulting in failed inflammation suppression/regulation. NOD-2 and A20 have specifically been found to be strongly associated with pediatric IBD. Gut commensals are known to exert anti-inflammatory activities towards NF-κβ and can have a potential role in attenuating inflammation that likely occurs due to microbial dysbiosis in IBD. Failure to terminate/downregulate NF-κβ signalling results in chronic inflammation in IBD. Well-regulated control of inflammation in children with IBD can help better control the disease and immune response. Better understanding of factors that control NF-κβ can potentially lead towards discovering targeted therapeutic interventions for IBD. Suppression of NF-κβ can be achieved through many modalities including anti-sense oligonucleotides (ASOs), siRNA (small interfering RNA), factors regulating NF-κβ, and microbes. This review focuses on the role of NF-κβ in pediatric IBD and potential therapeutic venues for attenuating NF-κβ-induced inflammation. Key words: Nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κβ), inflammatory bowel diseases (IBD), Crohn Disease (CD), ulcerative colitis (UC), immunity, microbes, homeostasis